Financial Consequences of The Introduction of The Fit For 55 On the Example of Poland - Justyna KUJAWSKA; Piotr KASPRZAK (Communications of International Proceedings, 2023)
In Europe and in Poland, there is a growing conviction that climate action is a necessity. When creating long-term strategies or making current decisions, companies are increasingly taking into account issues related to sustainable development and reducing CO2 emissions. Following the signing of the Paris Agreement in 2015, countries around the world pledged to reduce greenhouse gas emissions by 2050 so that the average temperature increase does not exceed 2°C, with the ambition to reach 1.5°C. EU countries have agreed to tighten climate regulations by adopting and implementing the Fit For 55 package.
Keywords: Fit for 55; climate; taxes; CO2; CO2 reduction